Comparison of the Bioactive Components in Two Seeds of Ziziphus Species by Different Analytical Approaches Combined with Chemometrics - Guo, Sheng; Duan, Jin-Ao; Li, Yiqun; Wang, Ruiqing; Yan, Hui; Qian, Dawei; Tang, Yuping; Su, Shulan (Frontiers in Pharmacology, 2017)
The Ziziphus species are considered to be the medicine and food dual purposes plants. Among them, the seed of Z. jujuba var. spinosa (ZS) has traditionally been used as an ethnomedicine in Asian countries for thousands years. Owing to the significant benefits for human health, the demand for ZS increased year by year, and the wild resources have become increasingly scarce, which resulted in a shortage of market supply for ZS and product adulteration by substituting ZS with the seeds of Z. mauritiana Lam. (ZM). However, whether the bioactivity of ZM is similar to ZS has not been fully confirmed till now. Thus, to provide potential information for evaluating the similarity of the health promoting activities between these two Ziziphus seeds, their chemical profiles, including triterpenoids, flavonoids, nucleosides, free amino acids and fatty acids were compared using HPLC-ELSD, UHPLC-TQ MS and GC-MS methods. Furthermore, a more holistic investigation was performed with multivariate PCA and OPLS-DA analyses to explore the relative variability between the seeds of two species. The results showed that a significant difference exists between ZS and ZM, and ZS was more rich in saponins, polyunsaturated fatty acids and some amino acids, whereas ZM was particularly rich in saturated fatty acids and flavonoids. The above results suggested the bioactivities of ZM for human health may not be similar to ZS owing to their difference in chemical profiles. These results would also be helpful for distinguishing the ZM from ZS with the chemical markers obtained from the study, and set a scientific foundation for establishing the quality control method of ZS.